The Characterisation of Joseph by Matthew (Matt 1–2; 13:55) - Mielcarek, Krzysztof (The Biblical Annals, 2023)
The article presents the figure of Joseph and his place in the narrative by the first evangelist in Matt 1–2. Apart from the arguments for the unifying function of Mary’s spouse in the whole Infancy Narrative, the most important features of Joseph highlighted by Matthew are emphasised. Those include the attitude of the righteous man, the fact of belonging to the royal family of King David, the bond and similarity to the actions of the patriarchs, as well as the silent and ascetic nature of the spouse and parent. Despite many similarities to the Lukan narrative, the first evangelist stresses different aspects in his characterisation of Joseph. Using the tools proposed by Cornelis Bennema, the author of the paper also assesses the degree of characterisation of the person under study, his role in the narrative and his representative value for the modern reader.